Extending Work Life Can Employers Adapt When Employees Want to Delay Retirement? - Morrill, Melinda Sandler (W.E. Upjohn Institute, 2016)
This book examines the employer perspective on how to respond to the needs and desires of older workers to delay or prolong the transition from full-time employment to complete retirement.